1996
DOI: 10.1093/clinids/23.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Capnocytophaga canimorsus Septicemia in Denmark, 1982-1995: Review of 39 Cases

Abstract: Thirty-nine Danish cases of Capnocytophaga canimorsus septicemia were reviewed to determine the clinical course of this infection. The cases of septicemia were related to recent dog bites or other close contact with dogs. The period from the bite to the onset of symptoms ranged from 1 to 8 days. The mean age of the patients was 59.1 years (range, 28-83 years). Underlying conditions included previous splenectomy and alcoholism. Thirteen patients had previously been in good health. Common initial symptoms were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
190
1
8

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(211 citation statements)
references
References 40 publications
12
190
1
8
Order By: Relevance
“…Reported exposures include dog or cat bite, licking of ulcers, burns, or wounds, dog ownership, and even casual contact with dogs [8,11,16,22]. In one study of human C canimorsus infections [16], approximately 80% of patients had animal bite or animal contact with open wounds, and 20% had no known exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Reported exposures include dog or cat bite, licking of ulcers, burns, or wounds, dog ownership, and even casual contact with dogs [8,11,16,22]. In one study of human C canimorsus infections [16], approximately 80% of patients had animal bite or animal contact with open wounds, and 20% had no known exposure.…”
Section: Discussionmentioning
confidence: 99%
“…12 As illustrated in this case, even with prompt, effective antibiotic administration, C canimorsus infection can progress to DIC, multisystem organ failure, and death. 9 A lwoffii was also identified, but was almost certainly a contaminant. It is a gram-negative bacillus that is widely distributed throughout the environment.…”
Section: Commentarymentioning
confidence: 98%
“…8 Severe illness typically occurs in immunosuppressed patients, particularly those with asplenia or cirrhosis. 9,10 The pathophysiology of fulminant C canimorsus infections is not well described. It has been suggested that certain strains may produce a toxin that inhibits macrophages and inactivates tumor necrosis factor in humans, although this is not yet widely accepted.…”
Section: Commentarymentioning
confidence: 99%
“…The remaining 10.5% of cases have no identifiable source of infection (5). Other reviews support the high frequency of a dog bite etiology in human infections ranging from 43 to 56% of cases (2,3,7). Infection typically occurs 2 to 3 days after contact, while some infections take up to 4 weeks to appear (5).…”
mentioning
confidence: 98%
“…C. canimorsus has been reported in approximately 125 cases of human infection (7). In a review of 103 cases, the most common clinical presentation was septicemia (94 cases).…”
mentioning
confidence: 99%